Pembelajaran Tari Rodat di Kelas VIII SMP YWKA Palembang: Penelitian - Nadira Puspita Sari; Nugroho N.A.D.; Muhsin Ilhaq (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to understand how eighth-grade students at SMP YWKA Palembang learn Rodat Dance. The approach used is descriptive qualitative research, with data collection methods including observation, interviews with teachers and students, and documentation. The results indicate that the learning process proceeded well. This success was influenced by the teacher's active involvement in creating a supportive learning environment, structured delivery of material, and the use of appropriate learning media. Students also showed high enthusiasm and active participation throughout the learning. Despite initial challenges, they successfully mastered the basic movements of Rodat Dance.